PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK ASAL MULA GUNUNG KELUD DALAM MENINGKATKAN LITERASI BUDAYA SISWA KELAS IV SEKOLAH DASAR - Nency Amalia Febrisa; Alfi Laila; Agus Budianto (Jurnal Manajemen Pendidikan, 2026)
This study was conducted in response to the low cultural literacy and narrative text comprehension of fourth-grade elementary school students. The study aimed to determine the validity, practicality, and effectiveness of the comic learning medium “Asal Mula Gunung Kelud” in improving students' cultural literacy. The research used a Research and Development approach with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The subjects were teachers and fourth-grade students of SDN Klepek. Data were collected through need assessment questionnaires, expert validation sheets, teacher and student practicality questionnaires, and pre-test and post-test instruments. The data were analyzed using percentage criteria and pre-test/post-test comparison supported by statistical testing. The results showed that the medium was valid, with media expert validation reaching 86% and material expert validation reaching 84%. The practicality results were also very high, with teacher and student responses reaching 98% and 95.66% in the large-scale trial. The effectiveness test showed an increase in the average score from 47.9 in the pre-test to 91.7 in the post-test. Therefore, the comic learning medium is valid, practical, and effective for improving cultural literacy through narrative text learning in elementary school.